Research on the transport behavior of microparticle proppants inside natural fractures - Liu, Huifeng; Wang, Xiaohan; Xu, Ning; Chen, Zhangxin; Peng, Yan (Frontiers in Earth Science, 2024)
volume of microparticle proppants inside fractures. When the width ratio of multi-branch fractures exceeds 2, this effect becomes obvious. (4) Particle size has an effect on proppant placement. 200mesh proppants can obtain uniform distribution of proppants among natural fractures. 140-mesh proppants can obtain maximum proppant volume among natural fractures. Sand concentration significantly affects proppant placement performance. The optimal sand concentration is 60kg/m 3 .The pumping rate for a single cluster fracture should not be excessively low. The pumping rate should be larger than 0.5m 3 /min and the optimal pumping rate 2m 3 /min.